Religion in a Japanese Cultural Perspective - Fatonah (Proceeding International Conference on Malay Identity, 2021)
Abstract: This research was a qualitative research with descriptive phenomenological approaches and library study. Phenomenological perspective in this research was used to describe religious phenomena in the Japanese society perspective and to see further about the behavior, motivation, actions that is done by Japanese students in interpreting religion in a cultural perspective. This study also aimed to understand the characteristics of the Japanese society in interpreting religion and culture. The focus of this research was an understanding of Japanese society way of life in interpreting religion and culture. The results of this study showed that the true religion in Japan was understood and lived with lightly, not binding. Almost all religious activities in Japan rely on the idea of ​​genze riyaku. It doesn't matter Buddha or Shinto. It is not different than treating other dimensions of material life. "If it is seen in their life, Japanese society can perform several religious rituals at once but not a few Japanese society who do not believe in the existence of God, it means that some of society who does not have any religious grip in their daily lives. Although many people consider that for Japanese society, religion is not so important. But there are also other opinions that see that the Japanese society really love their religion and beliefs, so it's no wonder, in Tokyo, there are so many temples that were built since hundreds of years ago. It can be concluded that religion in Japan is understood and lived with lightly, without binding. That is caused of their relaxed attitude in manifesting religion or beliefs. Religion in Japan is inseparable from culture and religion is not the main thing in their lives but in daily practice their lives are inseparable from the religions that have been inherent in culture. They keep bringing religion into their daily lives in the form of cultural symbols. Keywords: religion, culture, Japan